Improving DES Robustness for Text Encryption via Blum-Blum-Shub Key Generation - Moata, Omega Joel Patria; Vebiyatama, Andicha; Indra, Muhamad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The security vulnerabilities of the Data Encryption Standard (DES) require innovative enhancements to ensure data protection against modern threats. This study integrates the Blum-Blum-Shub (BBS) pseudorandom number generator with DES to enhance encryption robustness. By leveraging BBS’s randomness, the proposed method strengthens the 16-round block cipher structure of DES, improving security while maintaining computational efficiency. A Java-based desktop application is developed to implement this approach, ensuring data security without cloud reliance. Feasibility testing confirms successful encryption with an average processing time of 2 seconds, demonstrating both security improvements and practical applicability. Comparative analysis reveals that BBS integration enhances unpredictability, making decryption more challenging. The findings suggest that combining DES with BBS provides a viable solution to DES’s limitations. Future research may explore scalability, adaptation to diverse data types, and further optimizations to enhance encryption strategies against evolving cybersecurity challenges.